Forecasting rice yields in Gangetic West Bengal using rainfall and agricultural technology (MAUSAM, 1989)
The traditional method of linear multiple regression has been employed systematically to develop regression models to forecastrice yields in Gangetic West Bengal by using direct and derived parameters of rainfall, introducing technological trend and existing the series subsequently every year. The analysis of variance revealed that all regression models were highly significant  1%. The yields estimated by the models for all sample years lay within +- 10 %. The regression models explained more than 80 per cent of total variation In yields with multiple correlation coefficients exceeding 0.90.